IMPLEMENTATION OF COLLABORATIVE MULTIMODAL TEACHING TO DEVELOP STUDENT TEACHERS’ COMPETENCIES - Vina Nurviyani; Jauhar Helmie; Trini Handayani; Muhamad Syamsul Taufik; M. Budi Mulyadi (Publikasi Pendidikan, 2023)
Abstract: In the digital era, learners gain knowledge from various modes or multimodal. However, it is not in line with the Indonesian teachers’ competencies, particularly in conducting multimodal teaching. For the reasons, this study explored the development of student teachers’ competencies through collaborative multimodal teaching using VR. Moreover, it investigated the difficulties encountered by student teachers in developing the teacher competencies through collaborative multimodal teaching. The teacher competencies consist of the pedagogical, professional, social, and personal competencies (Ministry of National Education, 2007). This study applied qualitative design (multi-case study) involving 45 student teachers studying at three different study programs and 15 model teachers teaching at elementary schools in Cianjur, West Java. Three instruments were employed for the data collection of this study, i.e., observations, questionnaires, and interviews. The results indicate that the collaborative multimodal teaching (using VR) among the model teachers and the student teachers is conducted in five stages, i.e., observing, planning, simulating, practicing, and evaluating. In collaborative multimodal teaching using VR, students teachers involved in a group of teaching using VR as the instructional media naturally, get the transformation of pedagogical knowledge, and practice multimodal teaching directly in the natural teaching-learning processes. Moreover, it fosters the student teacher to develop the teacher competencies optimally, such as practicing teaching methodology and implementing multimodal teaching using VR in real-life contexts (pedagogic competence), expanding digital knowledge (e.g., VR), and utilizing it in teaching-learning processes (professional competence), showing pride in being future teachers (personal competence), interacting and communicating with the teachers and learners naturally (social competence). Thus, they are more ready to be future professional teachers in the millennial era. Nevertheless, they should keep learning and developing the teacher competencies (exceptionally professional and pedagogic competencies) to overcome teaching difficulties, such as learner characteristics, teaching management, material evaluation, curriculum development, and assessment.